Behavioral Macroeconomics and Macroeconomic Behavior - Akerlof, George A (American Economic Review, 2002)
Think about Richard Scarry’s Cars and Trucks and Things That Go. Think about what that book would have looked like in sequential decades of the last century had Richard Scarry been alive in each of them to delight and amuse children and parents. Each subsequent decade has seen the development of ever more specialized vehicles. We started with the Model T Ford. We now have more models of backhoe loaders than even the most precocious fouryear-old can identify. What relevance does this have for economics? In the late 1960’s there was a shift in the job description of economic theorists. Prior to that time microeconomic theory was mainly concerned with analyzing the purely competitive, general-equilibrium model based upon profit maximization by firms and utility maximization by consumers. The macroeconomics of the day, the so-called neoclassical synthesis, appended a fixed money wage to such a generalequilibrium system. “Sticky money wages” explained departures from full employment and business-cycle fluctuations. Since that time, both microand macroeconomics have developed a Scarry-ful book of models designed to incorporate into economic theory a whole variety of realistic behaviors. For example, “The Market for ‘Lemons’ ” explored how markets with asymmetric information operate. Buyers and sellers commonly possess different, not identical, information. My paper examined the pathologies that may develop under these more realistic conditions. For me, the study of asymmetric information was a very first step toward the realization of a dream. That dream was the development of a behavioral macroeconomics in the original spirit of John Maynard Keynes’ General Theory (1936). Macroeconomics would then no longer suffer from the “ad hockery” of the neoclassical synthesis, which had overridden the emphasis in The General Theory on the role of psychological and sociological factors, such as cognitive bias, reciprocity, fairness, herding, and social status. My dream was to strengthen macroeconomic theory by incorporating assumptions honed to the observation of such behavior. A team of people has participated in the realization of this dream. Kurt Vonnegut would call this team a kerass, “a group of people who are unknowingly working together toward some common goal fostered by a larger cosmic influence.” In this lecture I shall describe some of the behavioral models developed by this kerass to provide plausible explanations for macroeconomic phenomena which are central to Keynesian economics. For the sake of background, let me take you back a bit in time to review some history of macroeconomic thought. In the late 1960’s the New Classical economists saw the same weaknesses in the microfoundations of macroeconomics that have motivated me. They hated its lack of rigor. And they sacked it. They then held a celebratory bonfire, with an article entitled “After Keynesian Macroeconomics.” The new version of macroeconomics that they produced became standard in the 1970’s. Following its neoclassical synthesis predecessor, New Classical macroeconomics was based on the competitive, general-equilibrium model. But it differed in being much more zealous in insisting that all decisions—consumption and labor supply by † This article is a revised version of the lecture George A. Akerlof delivered in Stockholm, Sweden, on December 8, 2001, when he received the Bank of Sweden Prize in Economic Sciences in Memory of Alfred Nobel. The article is copyright © The Nobel Foundation 2001 and is published here with the permission of the Nobel Foundation.